REKONSTRUKSI KEBEBASAN HAKIM DALAM MEMUTUS PERKARA PIDANA BERBASIS HUKUM PROGRESIF - Safni Kholidah Hasibuan; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
As the evolution continues to grow from the scientific side, the idea to establish the existence of jurisprudence to be, True science is also growing. It should be noted carefully that in taking legal action or law enforcement then, law enforcement does not solely work only to see the law in its foundation as the rule of law only, but also should build on the foundations of other, more important, the bases were formulated by Radbruch law as a fundamental value, namely,certainty,justice,andexpediency. Judicial independence is the guarantee of the implementation of independent judicial power as outlined in the Judicial Authority Act No. 48 of 2009 states that " Judicial Power is an independent power to organize court to uphold law and justice . The purpose of this thesis is ; to know the practice of judges in deciding the case of criminal law based Progressive. Second; to know new construction build a legal culture based progressive law judges in realizing a true and fair verdict and protect the public interest.Progressive judges are judges who adhere to the flow of progressive law. The word comes from the progressive progressi means is progress. So here is expected that the law should be able to keep abreast of the times, able to answer the changing times with all the basic therein, and able to serve the community by leaning on the aspects of morality and human resources law enforcement sendiri.Jenis research / approach used by the authors is a normative study , with the approach of Legal Theory and principles of the law. Because it makes the literature as the main pedestal. From the research problem there are two main things that can be inferred, first, entrance to the progressive application of the law in the practice of the courts in Indonesia, has been formally granted by Act No. 48 of 2009 on Judicial Power. Second, in practice at the Criminal Court, has begun characterized by a progressive way of thinking, but a way of thinking is still the mainstream of legal positivism among the judges of the courts in dealing with criminal matters.Progressive law presented extremely relevant and important to base and referral cultural reconstruction law judges in handling criminal cases in court. Advice writer, first, in the practice of criminal justice tradition of thinking that the progressive need to be supported, in order to truly become a legal culture among judges in handling criminal cases that the judge's decision is fair, correct and protect the interests of society and the immediate ratification of the draft Law Book of the Law criminal Indonesia, to make it clear that in addition to the written law/ legislation. Second, the judge in deciding a criminal case in court should not be too captive to the law, to violate the laws of justice it has obtained valid, provided that the judge may account for its decision. And the need to insert the material / progressive method of teaching law at the University to broaden the students on legal issues in their entirety.Keywords: Progressive Law – Reconstruction - Legal Positivism